Clinical relevance of mutant NPM1 and CEBPA in patients with acute myeloid leukaemia – preliminary report - Helbig, Grzegorz; Wozniczka, Krzysztof; Wieclawek, Agnieszka; Soja, Anna; Bartkowska-Chrobok, Aleksandra; Kyrcz-Krzemien, Slawomira (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: Mutant NPM1 and CEBPA have been reported in patients with acute myeloid leukaemia (AML) and intermediate cytogenetic risk, and they appear to be associated with characteristic demographic and laboratory data, as well as clinical outcome. The objective of the study was to assess the clinical relevance of NPM1 and CEBPA mutations in AML. Material and methods: This retrospective analysis was based on 60 newly diagnosed patients with AML and normal/no metaphases karyotype and known mutation status, who were treated in our centre between 2008 and 2011 according to the PALG (Polish Adult Leukaemia Group) study protocol. Pretreatment bone marrow samples were studied by G-banding analysis, and NPM1 , CEBPA , and FLT3-ITD mutations were detected by polymerase chain reaction (PCR). Results : NPM1 mutations were detected in 21 AML patients (35%). In the NPM1 -positive subgroup, the FLT3-ITD mutation was observed in 3 cases (14%), which was significantly less frequent than in the NPM1 -negative patients, where FLT3-ITD was detected in 16 cases (41%; p = 0.04). Among the CEBPA -positive population (n = 11; 18%), none of the studied patients had FLT3-ITD mutation, whereas it was detected in 19 CEBPA -negative patients (0% vs. 38%; p = 0.01). The highest complete remission rate was reported for the NPM1 -positive/ FLT3-ITD -negative group (n = 18; 88%) and the CEBPA -positive/ FLT3-ITD -negative group (n = 8; 73%). For OS, multivariable analysis revealed NPM1 -positive/ FLT3-ITD -negative (HR: 0.18, 95% CI: 0.19–0.63) and CEBPA -positive/ FLT3-ITD -negative (HR: 0.35, 95% CI: 0.19–0.63) as favourable prognostic factors. The presence of the NPM1 -negative/ FLT3-ITD -positivecombination predicted adverse overall survival (HR: 2.03, 95% CI: 1.13–3.66). Conclusions: NPM1 and CEBPA mutations are associated with clinical outcome in AML patients.